Beyond LAVs: corruption, commercialization and the Canadian defence industry - Gutterman, Ellen; Lane, Andrea (Canadian foreign policy journal, 2017)
The Trudeau government's decision to uphold a 2014 contract to sell CAD $15 billion worth of military equipment to Saudi Arabia has attracted considerable controversy in Canada, garnering both opposition and support. Yet public discussion of the Canada-Saudi light armored vehicle (LAV) contract has sidestepped the most serious problems raised by Canada's escalation of its involvement in the international arms market through this sale: the violence and corruption of the international arms trade, to which this sale contributes; the subordination of Canadian foreign policy and of international peace and security to commercial aspirations and the short-term interests of electoral politics, which this contract evinces; and the questionable importance of the Canadian defence industrial base, upon which arguments in favor of this contract rely. Given both the political and economic salience of defence industry jobs in the 2015 election and the export-driven nature of Canada's defence industry, Canadians should not be surprised by the Canada-Saudi LAV deal. The real question, however, is whether Canada should support its own defence industrial base, whatever the costs and contribution to corruption - or not.